Porphyrin precursors and porphyrins in three patients with acute intermittent porphyria and end-stage renal disease under different therapyREGIMES - Sardh, E; Andersson, D E H; Henrichson, A; Harper, P (Cellular and Molecular Biology, 2015)
Porphyrin precursors and porphyrins were measured in three patients with recurrent attacks of acute intermittent porphyria and end-stage renal disease (ESRD): Two patients on hemodialysis and one on peritoneal dialysis. Plasma porphobilinogen (PBG) and porphyrins were considerably increased in the three patients. In a previous study, the mean urinary and plasma PBG/ALA ratio in biochemically active AIP patients with conserved renal function was 2.0 (normal 0.3) and plasma porphyrin levels were normal (< 10 nmol/L). In this study we show that the progression to ESRD was paralleled by an increase in urinary and plasma PBG/ALA ratio reaching levels above 6 and higher. Plasma porphyrin increased to levels above 1000 nmol/L causing cutaneous lesions resembling porphyria cutanea tarda. The porphyrin precursors were readily filtered by dialysis membranes but not the porphyrins. The development of kidney failure was a devastating complication in these AIP patients with chronic active disease, leading to unavoidable deterioration of peripheral veins, progression of peripheral neuropathy, dialysis treatment and secondary cutaneous lesions. The clinical course could not be reversed by medical treatment in any of the cases. Today, combined liver and kidney transplantation should be considered as a therapeutic option.